Math, asked by anushka1374, 2 months ago

please give me the solution and I will mark you as a brainlist​

Attachments:

Answers

Answered by CopyThat
66

Answer :-

The zeroes are -√2 and 3√2 :

Step-by-step explanation :-

p(x) = x² - 2√2x - 6

Factorization by splitting the middle term :

x² - 2√2x - 6

x² - 3√2x + √2x - 6

x(x - 3√2) + √2(x - 3√2)

(x + √2) (x - 3√2) = 0

The zeroes are -√2 and 3√2 :

α = -√2

β = 3√2

a = 1

b = -2√2

c = -6

Sum of zeroes :

α + β = -b/a

-√2 + 3√2 = -(-2√2)/1

2√2 = 2√2

∴ L.H.S = R.H.S

Product of zeroes :

α × β = c/a

-√2 × 3√2 = (-6)/1

3 × -2 = -6

-6 = -6

∴ L.H.S = R.H.S

Similar questions
Math, 9 months ago